Banking Dilemmas: Unveiling Factors Affecting Muslim Preferences and Riba Perception in West Sumbawa - Ahlis Fatoni; Mega Tria Rizki Luik (IQTISHADUNA, 2023)
This study aims to explore Muslim’s preferences in selecting a bank and theirs understanding of rib?. Primary data collected from the Muslims in West Sumbawa was analysed using exploratory factor analysis by SPSS. It is found that Muslims in West Sumbawa has knowledge about rib?. However, Muslim customers still are attracted to conventional bank because of its facility, variety of products, and its media marketing. Regarding the misconception of rib?, level of education has relation in five conceptions in prohibiting of rib?. Religion variable also has significant relation in prohibiting rib?, while the occupation variable resulted the allowance of rib? as long as it is not excessive. The results suggest that as Muslim majority, the education of rib? should be taken by the Muslim organizations and or government, while Islamic bank should do more attractive marketing and open new branch to attract Muslim customers.